Relationship between Nurses\' Job Satisfaction and Burnout with Patients Satisfaction in Shiraz, 2012 - Hojjat Habibi; Alireza Mooghali; Kamran Bagheri Lankarani; Forouzan Habibi (Tehran University of Medical Sciences, 2014)
Background & Aim: Patients often build their perceptions about the quality of health services on the care provided for them in hospitals by nurses. The present study aimed to assess the relationship between the job satisfaction and burnout among nurses with patientschr('39') satisfaction in Shiraz hospitals in 2012 .   Methods & Materials: In this cross-sectional study, participants were selected through a multi-stage sampling . A total of 280 nurses and 560 patients were recruited to the study. Data were collected using the Spectorchr('39')s job satisfaction and the Maslach Burnout questionnaire s. The structural equation modeling and the confirmatory factor analysis were used to analyze the data in the SPSS and AMOS .    Results: There were significant relationships between the nurseschr('39') job satisfaction and burnout with the patientschr('39') satisfaction. Also , there was a negative and significant relationship between the job satisfaction with burnout among nurses (P<0.001) .   Conclusion: T he factors affecting job satisfaction and burnout among nurses should be considered in promoting health care provided by nurses .